(untitled) (Medical Forum Monthly, 2023)
Objective: To study the association between iron deficiency anaemia and body mass index in adolescent girls in a rural area of Pakistan. Study Design: Cross-sectional descriptive study. Place and Duration of Study: This study was conducted at the primary and secondary school of Nankana Sahib District, Pakistan in December 2022. Materials and Methods: A self-structured questionnaire was used for data collection to assess the nutritional status of 162 school-going girls in a rural setting of Pakistan. Data comprised of demographic details, their knowledge about healthy food, physical and clinical examination. Blood samples were taken for estimation of hemoglobin levels. As the data collected was not normally distributed, various non- parametric statistical tests were applied to look for association between iron deficiency anaemia and body mass index using SPSS version 25. Results: The results were interpreted using WHO BMI-for-age chart for adolescent girls (10-19 years) and WHO anemia categorization of mild, moderate, severe and no anaemia. Our study showed that among 162 girls, 67.3% had normal BMI, 8.0% were obese and 24.7% were lower weight. Majority of the girls (69.8%) had no anemia whereas mild and moderate anaemia was observed in 16.7% and 13.6% of the girls respectively. A weak positive correlation (coefficient r = 0.138) although statistically non-significant (p =0.08) was found between BMI and Hb levels in the studied subjects. Conclusion: High prevalence of anaemia is seen in adolescent girls with lower BMI.